Migration in Asia What skills for the future? - Gagnon, Catherine (OECD Development Policy Papers, 2021)
The world is increasingly facing a technologically changing employment landscape and such changes are directly affecting the future demand for skills. For regional economies built on labour migration, the impending changes will affect migrants and their families, their countries of origin and the recruitment systems they are attached to - and ultimately disrupt the development benefits of migration. This paper investigates how the future of the employment landscape will affect migration within the Abu Dhabi Dialogue, a regional consultative process for migration in Asia. It investigates the impending changes in the demand for skills in countries of destination, how such changes will affect migration processes and whether countries of origin are ready for the changes. It provides recommendations on how regional consultative processes can foster dialogue between key actors from both countries of origin and destination to better navigate future changes and ensure a smooth transition